The Effect Of Groundwater Level And Organic Mulch Application On The Chemical Properties Of Peat Soil - Vera Nursari; Delita Zul; Hapsoh Hapsoh (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Peat as agricultural land has various obstacles, one of the problems is the decrease in groundwater level. This can have an impact on the availability of nutrients in the soil. Therefore, water management is an absolute necessity for agricultural activities on peatlands. Another effort that can be made to increase the fertility of peatlands as agricultural land is to use organic mulch. This study aims to analyze the effect of peat water level and application of organic mulch on the chemical properties of peat soil planted with corn. This research was conducted in Air Terbit Village, Riau Province and the Soil Laboratory, Faculty of Agriculture, University of Riau, from February to July 2021. This research used a factorial complete randomized design (CRD) method consisting of 2 factors. The first factor was the various heights of the groundwater level which consisted of 3 levels (30 cm, 40 cm and 50 cm), while the second factor was various types of organic mulch (without mulch, mulch of empty oil palm bunches, mulch of rice straw and mulch of corn stover). The results showed that the GWL 30 cm treatment and rice straw mulch increased the pH, Ca and Mg values ​​better than the other treatments, the N element also increased at GWL 30 cm. In general, the two treatment factors also increased the values ​​of P, CEC and Na in some experimental units. C-organic and K values ​​decreased after the treatment compared to the criteria of the soil before treatment.